Quartz And Zircon as markers of the magmatic-hydrothermal evolution of the Antônio Vicente Granite, Velho Guilherme Intrusive Suite, Carajás Province - Claudio Nery Lamarão; Claudio Nery Lamarão; Claudio Nery Lamarão; Claudio Nery Lamarão (Geologia USP. Série Científica, 2013)
the Antônio Vicente Granite, Carajás Province, by scanning electron microscope-cathodoluminescence (SEM-CL) images. In the lessevolved rocks, containing amphibole and biotite, well developed anhedral to subhedral, luminescent and intensely fractured crystalsdominate, named Qz1. Hydrothermal fluids that percolated the granite modified the magmatic quartz (Qz1) into Qz2 and Qz3 throughprocesses of alteration, dissolution and recrystallization, with these changes much more evident in the intensely altered syenograniterocks. Qz4 constitute medium-to-coarse grained crystals, usually luminescent and comparatively little fractured. Its occurrence is restrictedto strongly hydrotermalized syenogranite rocks and bodies of greisens, suggesting the beginning of the greisenization process.In the greisens, medium-to-coarse grained euhedral, concentrically zoned quartz crystals dominate, with typical features of hydrothermalorigin (Qz5). Fine crystals of zoned cassiterite (≤ 100 μm) are common and fill cavities in the types Qz4 and Qz5. Zircon crystalsdominantly anhedral, corroded, with the highest contents of Hf and the lower Zr/Hf ratios belong to more evolved and hydrothermallyaltered rocks and to associated greisens, both carriers of Sn mineralization. This fact suggests that the geochemical signature of zircon,especially Zr/Hf ratio, can be used for the preliminary assessment of metallogenic potential of tin granites.